Music Performance Management Southburn Fest Volume 4 - Wicaksono, Galang Bimo (Repertoar, 2025)
The application of management strategies used in managing the Southburn Fest Vol . 4 event and the obstacles and solutions carried out in the management of Southburn Fest Vol . 4, including logistics, schedules, and infrastructure, are the problems in the research. The purpose of this study is to find out the application of performing arts management strategies, as well as the obstacles and solutions used by the Southburn Fest vol. 4 community. This research used descriptive qualitative research methods. This research was conducted in the city of Tulungagung. The subjects of this research are the founder of Southburn Fest and members of the Southburn community. Also, the object of this research is the management of the Southburn Fest Vol . 4 event. The findings in this study include the management strategy of Southburn Fest vol.4 using comprehensive concept planning, performer management, production management, finance and sponsorship, and effective promotion